Грызуны (Rodentia) деснянского позднего палеолита (пути становления фауны и ее палеогеографический анализ) - Рековец, Л.И. (Вестник зоологии, 1978)
The Late Pleistocene rodents from localities of the northern Ukraine (the Desna Paleolith) are represented by 13 species which differ from the present ones at the subspecies level. The character of changes in the rodent fauna of this region is traced from Late Pleistocene till the present time. The fauna is of mixed type represented both by Arctic (lemmings) and steppe (sousliks, jerboas, rainbows) species. Peculiarities of the morphological structure show that these species inhabited open tundra-steppe landscapes.